Not yet post-Asia: Paradoxes of identity and knowledge in transitional times. Issue 2 (1st October 2014) - Ang, Ien
We live in transitional times, in which the weight of global power is markedly shifting towards Asia. In this context the meaning of the category 'Asian' is thoroughly in flux, negotiated and contested across multiple dimensions. In this light, is it possible, or even desirable, to speak about post-Asia? If so, what could it mean? Or is such talk perhaps premature? In this article, I consider three ways of thinking about the notion of post-Asia: the temporal, the spatial and the epistemological. In all these instances, we can observe that a genuinely post-Asian perspective has not yet emerged.